1975
DOI: 10.1901/jeab.1975.23-271
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Size of the Test Environment on Behavior Under Two Temporally Defined Schedules

Abstract: The effect of the size of the floor area of the operant test chamber on behavior was tested using a standard-size test chamber and a test chamber with one-fourth of the floor area of the standard chamber. Two groups of pigeons were tested under a differential-reinforcement-of-low-rate 15-sec schedule or a variable-interval 60-sec schedule. Both groups of pigeons had higher response rates while in the smaller floor area. Pigeons under the differential-reinforcement-of-low-rate schedule also showed a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
3

Year Published

1977
1977
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
0
16
1
3
Order By: Relevance
“…Maintained responding showed little influence on the restrainer with the exception of short ITI values where stable keydirected responding may not be reliably observed in unrestrained subjects. In previous work somewhat higher response rates have been observed for restrained as compared to unrestrained subjects in differential-reinforcement-of-low-rate (DRL) schedules (Richardson & Loughead, 1974;Skuban & Richardson, 1975). Of course higher rates in this procedure generally covary with lower rates of reinforcement.…”
Section: Discussionmentioning
confidence: 87%
“…Maintained responding showed little influence on the restrainer with the exception of short ITI values where stable keydirected responding may not be reliably observed in unrestrained subjects. In previous work somewhat higher response rates have been observed for restrained as compared to unrestrained subjects in differential-reinforcement-of-low-rate (DRL) schedules (Richardson & Loughead, 1974;Skuban & Richardson, 1975). Of course higher rates in this procedure generally covary with lower rates of reinforcement.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to Staddon and Simmelhag (1971) and Staddon and Ayres (1975) Finally, the present experiment confounded activity and distance from the lever, and chamber size is related to performance with DRL schedules (Skuban & Richardson, 1975 …”
Section: Collateral Activities-sequential Propertiesmentioning
confidence: 80%
“…) will be affected by the nature of the stimuli correlated with food presentation (Timberlake, Wahl, & King, 1982), there is little evidence that any schedule-induced activity, except drinking, has been raised above its operant level (Roper, 1981). Moreover, schedule-induced drinking may be amenable to an interpretation based on normal reinforcement mechanisms (Keehn & Riusech, 1979 (Skuban & Richardson, 1975) or providing stimuli for collateral activities may both serve a common function. Second, collateral activities assume no special status as a response class with regard to the operant.…”
Section: Discussionmentioning
confidence: 99%
“…The complementary observation has also been made. Several investigators have shown that when collateral responses are restricted to the area just surrounding the operandum, DRL efficiency has decreased (Glazer & Singh, 1971;Richardson & Loughead, 1974;Skuban & Richardson, 1975).…”
Section: Stereotypy and Heterogeneity Of Collateral Behaviormentioning
confidence: 99%